KERAGAMAN FENOTIPE KELAPA DALAM DI KECAMATAN TENGA KABUPATEN MINAHASA SELATAN - Frederik Joseph Pomantow; Arthur . Pinaria; Wenny . Tilaar (AGRI-SOSIOEKONOMI, 2016)
North Sulawesi province is known as one of the biggest coconut production in Indonesia. South Minahasa Regency is the biggest coconut production in the North Sulawesi Province. District of Tenga is one of major coconut production in South Minahasa Regency. Therefore, effort should be conducted in order to maintain the coconut production in District of Tenga. One effort to maintain coconut production in District of Tenga is to cultivate coconut varieties which can result high yield. High yield production of coconut can be resulted through plant breeding. In plant breeding, variation is parameter of selection that can be used to evaluate population performance of breeding material. The variation of coconut in District of Tenga has not been investigated. In order to support selection program to produce good quality of coconut varieties it is important to assess coconut population in District of Tenga. Research was conducted by collecting samples at four villages namely Tawaang, Tawaang Barat, Radey and Malinow representing in District of Tenga. Sample was collected using purposive sampling. Twenty-five sampels of coconut tree were collected at each village. Samples of coconut tree were collected using purposive sampling followed by marking of each sample. Characters observed were number of fruit per tree, number of fruit per bunch, fruit weight per bunch, fruit weight without husk per bunch, fruit weight without water per bunch, coconut shell weight per bunch and fresh fruit meat (white flesh) weight per bunch. Data was analyzed using Bartlett homogeneity test. Result showed that characters of number of fruit per tree and fruit weight without husk per bunch were varied. Whereas, characters number of fruit per bunch, fruit weight without husk per bunch, fruit weight without water per bunch, coconut shell weight per bunch and fresh fruit meat (white flesh) weight per bunch were not varied.Keywords: Coconut, Variation, Fenotype, Tenga District, South Minahasa